Forest recreation - Douglass, Robert W. (Pergamon Press, 1982)
Forest Recreation focuses on the increasing consideration of forests as destination for recreation. The book aims to put together the findings of researchers on the issues and problems that confront forest recreation administrators and the demands of the public. The selection also offers guidance to forest land managers with respect to the basic requirements of forest recreation as well as in planning. The book starts by defining outdoor recreation, including history and the factors affecting this type of recreation. The text then gives information on the number of forest recreation areas and.